The Effect of Reward System, Job Satisfaction, Career Development, Work Culture and Work Motivation on Employee Work Discipline at Karunia Indah Medika Hospital Muara Enim - Nadia Dwi Karisna; Abdul Basyith; Nisma Aprini (Universitas Dehasen Bengkulu, 2026)
This study aims to analyze the influence of the reward system, job satisfaction, career development, work culture, and work motivation on employees’ work discipline at Karunia Indah Medika Hospital, Muara Enim. This research employed a quantitative approach with a survey method. The population consisted of 160 employees, and all members of the population were selected as respondents using a total sampling technique. Data were analyzed using multiple linear regression analysis. The results indicate that simultaneously the reward system, job satisfaction, career development, work culture, and work motivation have a significant effect on employees’ work discipline (F = 57.447; sig. = 0.000; Adjusted R² = 0.640). Partially, work culture and work motivation have a significant effect on work discipline, whereas the reward system, job satisfaction, and career development do not have a significant effect on employees’ work discipline.